A novel broadband reflectarray antenna employing equivalent magnetic dipole elements - Sen Li; Yang Cai; Hong Ma; Lijun Bu; Siyu Qi; Yufan Cao; Tao Wu (Scientific Reports)
Abstract In this paper, a planar reflectarray antenna employing equivalent magnetic dipole (EMD) elements is proposed. An H-shaped patch and two coupling T-shaped patches are employed as the EMD element, in which the electric current intrinsically flows on the central H-shaped patch while the equivalent magnetic current with orthogonal direction can be ingeniously excited in the meanwhile due to the adjacent patch gaps. Compared with conventional magnetoelectric dipoles, the single-layer EMD element eliminates the vertically metallized via structure and generates an equivalent magnetic dipole with the help of displacement current rather than toroidal current, providing benefits including reduced complexity and enhanced bandwidth. A prototype reflectarray composed of 16 × 16 elements is experimentally designed and the achieved 1.5-dB gain bandwidth of 33.3% (9.5- 13.3 GHz) and the peak gain of 27.5 dBi with the peak aperture efficiency of 57% are well validated the proposed concept. With excellent broadband performance, high gain, and high aperture efficiency, the developed reflectarray antenna serves as a promising device for high-speed data transmission communication in the X-band.